Adherence of healthcare providers and Midwifery on the Implementation of Clinical Practice Guidelines in primary healthcare settings: facilitators and barriers at KSA - Abeer Talal Alotaibi; Amal Saad Masaad Almutairi; Amal Ali Abdurahman Alotaibi; Reem Menawer Falah Alzabni; Mansour Marzouq Alotaibi; Mubarak Mohammed Mubarak Al Otaibi; Ayedh Mohammed Marzouk Al Otaibi; Fahad Salman Almajnoni; Hamdan Dhafer Al-Asimi; Moqeid Gaied. Moqeid Alotaibi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Clinical practice guidelines (CPGs) are essential tools designed to standardize care, improve patient outcomes, and promote evidence-based practices in healthcare. Adherence to these guidelines is particularly critical in primary health care settings, where diverse conditions, including chronic diseases and maternal health needs, are managed. Despite their importance, variations in adherence and implementation persist, often due to barriers such as insufficient training, resource limitations, and systemic challenges, highlighting the need for further investigation. Aim of the study:assess the level of CPG adherence of among healthcare providers and midwifery in primary health care settings in this country and identify the related barriers. Methods: Cross sectional, descriptive research design was utilized to conduct this research at It was conducted at 10primary healthcare settings , at Jeddah at Saudia Arabia ; Subjects:300 participants were assigned conveniently to participate in this research out of 789 healthcare providers and midwifery selected they were classified into general practitioner, Family physician consultant, Family physician specialist, Nurses, Midwifery, and Nursing technicians. They inclusion criteria was having at least 1-yearexperience and welling to participate in the research. Results:The majority of participants (98.0%) acknowledged using CPGs in their everyday practices. The high implementation rates of guidelines for diabetes (91.3%), hypertension (81.2%), and hyperlipidemia (69.8%) suggest that healthcare providers prioritize chronic disease management, which might reflect the burden of these conditions in the population. Table 2 shows that guidelines for postnatal care (38.9%) and women’s screening (45.6%) were the least implemented. According to Table 2, the top two reasons for following CPGs were their evidence-based nature (79.2%) and their coverage of common clinical scenarios (43.6%). In addition, Table 4 findings indicate that most healthcare providers and midwives are receptive to CPGs and find them practical to implement, reflecting high adherence potential. However, the desire for further learning emphasizes a critical barrier that must be addressed to improve adherence across all guideline areas. Tailored training programs, especially in underserved areas like women’s health, could help bridge these gaps and enhance overall CPG implementation in primary healthcare settings. Conclusion:This study highlights a high level of adherence to clinical practice guidelines (CPGs) among healthcare providers and midwifery in primary health care settings, particularly in managing chronic conditions such as diabetes, hypertension, and hyperlipidemia. However, gaps in adherence were observed in areas like postnatal care and women’s health screening, indicating the need for targeted efforts to address these deficiencies.